Just health care - Daniels, Norman 1942- (Cambridge University Press, 1985)
How should medical services be distributed within society? Who should pay for them? Is it right that large amounts should be spent on sophisticated technology and expensive operations, or would the resources be better employed in, for instance, less costly preventive measures? These and others are the questions addreses in this book. Norman Daniels examines some of the dilemmas thrown up by conflicting demands for medical attention, and goes on to advance a theory of justice in the distribution of health care. The central argument is that health care, both preventive and acute, has a crucial effect on equality of opportunity, and that a principle guaranteeing equality of opportunity must underly the distribution of health-care services. Access to care, preventive measures, treatment of the elderly, and the obligations of doctors and medical administrations are fully discussed, and the theory is shown to underwrite various practical policies in the area
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Medical ethics; Medical policy; Social medicine; Gerechtigkeit; Gesundheitswesen; Soziale Gerechtigkeit; Gesundheitsfürsorge; Ethik; Medizinische Versorgung